Scholarly Ethics and Academic Integrity in the Study of the Qur'an and Tafsir in the Digital Era - Dedi prayoga Prayoga; Nala Haifa Basma (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
The rapid development of digital technology has transformed the study of the Qur'an and its interpretation by expanding access to knowledge through the internet, social media, artificial intelligence, and digital platforms. While these innovations facilitate the dissemination of Islamic scholarship, they also raise ethical concerns, including plagiarism, misinformation, algorithmic bias, and the decline of academic authority. This study aims to examine the concept of academic ethics in the digital era and its application in Qur'anic studies and interpretation. Using a qualitative approach with descriptive-analytical methods, this research employs philosophical, normative-ethical, and Islamic perspectives. Data were collected through documentary analysis of scholarly literature, digital sources, and religious social media content, and analyzed using content analysis. The findings indicate that academic ethics in the digital context requires the integration of honesty, transparency, responsibility, and scientific accountability with digital literacy. These principles are essential to ensure that technological advancement supports the integrity, credibility, and authenticity of Qur'anic scholarship while preventing the spread of misleading interpretations and maintaining public trust in academic research.Keywords:Scientific ethics, the Qur’an, the digital age